Application of Blended Learning in Physical Education: Article Review - Akbar Syafruddin; Suparman Suparman (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
The writing of this article aims to examine the implementation of blended learning-based physical education and sports learning. Article searches were carried out by utilizing the Google Scholar media published in the last 10 years, with a total of 10 articles related to the application of blended learning in physical education learning. The conclusion in this review is that Blended learning provides convenience and efficiency in the implementation of physical education learning, through blended learning it provides convenience for students to access various materials related to learning in physical education.